Advanced pharmacological therapies for neurofibromatosis type 1-related tumors - Foiadelli , Thomas; Naso, Matteo; Licari, Amelia; Orsini, Alessandro; Magistrali, Mariasole; Trabatti, Chiara; Luzzi, Sabino; Mosconi, Mario; Savasta, Salvatore; Marseglia, Gian Luigi (Acta Biomedica Atenei Parmensis, 2020)
Neurofibromatosis Type 1 (NF1) is an autosomal dominant tumor-predisposition disorder that is caused by a heterozygous loss of function variant in the NF1 gene, which encodes a protein called neurofibromin. The absence of neurofibromin causes increased activity in the Rat sarcoma protein (RAS) signalling pathway, which results in an increased growth and cell proliferation. As a result, both oncological and non-oncological comorbidities contribute to a high morbidity and mortality in these patients. Optic pathways gliomas, plexiform neurofibromas and malignant peripheral nerve sheath tumor (MPNST) are the most frequent NF1-associated tumors. The treatment of these complications is often challenging, since surgery may not be feasible due to the location, size, and infiltrative nature of these tumors, and standard chemotherapy or radiotherapy are burdened by significant toxicity and risk for secondary malignancies. For these reasons, following the novel discoveries of the pathophysiological mechanisms that lead to cell proliferation and tumorigenesis in NF1 patients, emerging drugs targeting specific signalling pathways (i.e. the MEK/ERK cascade), have been developed with promising results.